Sustainable and inclusive – Evaluating urban sustainability indicators' suitability for measuring progress towards SDG-11. (October 2021) - Thomas, Ryan; Hsu, Angel; Weinfurter, Amy
The adoption of the sustainable development goals marks a transition in the global sustainability discourse to a growing focus on equity, with urban areas' role in achieving sustainable and inclusive growth more explicit in sustainable development goal-11. Within this discourse, urban sustainability indicators could be used to monitor environmental quality and equity within individual cities, while promising to deepen our understanding of how urban areas contribute to global environmental sustainability. We examine 484 indicators of urban and regional environmental sustainability sourced from 40 indexes and online data repositories to determine their suitability for measuring both urban environmental performance and equity. Despite the large number of existing indicators related to urban environmental monitoring, we find that they are inadequate as tools for evaluating progress towards sustainable development goal-11's integrated goal of sustainable and inclusive (i.e. equitable) urban areas, due to a lack of benchmarks, targets, and explicit measurement of equity considerations. Future research should emphasize data collection that can be disaggregated geographically to make it possible to measure distributional equity and establish locally appropriate benchmarks and realistic targets for urban sustainability indicators. Lastly, we argue that utilizing large-scale, high-resolution datasets has the potential to help overcome these data collection challenges.